1985
DOI: 10.1007/bf00269208
|View full text |Cite
|
Sign up to set email alerts
|

Suspension culture of sugarbeet (beta vulgaris L.). induction and habituation of dedifferentiated and self-regenerating cell lines

Abstract: A systematic procedure is described to obtain habituated cell suspensions from different explant sources of sugarbeet (Beta vulgaris L.).Cytokinin habituation occurred spontaneously. Auxin habituation could be induced by successive lowering of the external hormone concentration. Habituation was reversible and independent of the cell type or explant source. The habituated nature of the cells was lost during regeneration and had to be reinduced by adequate treatments.A method for initiating habituated self-regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Hormone free growth of root or shoot organ cultures was not attempted. Other work has shown the ability of sugar beet cells (callus and suspension) to habituate to hormone-free medium by successively lowering the auxin concentration, however the ability to grow without exogenous cytokinins appeared to be spontaneous in most of these cultures (Van Geyt and Jacobs, 1985). Doubling times of these cell cultures ranged from 4 to 8 days, similar to that of the rye root cultures reported here.…”
Section: Discussionsupporting
confidence: 59%
“…Hormone free growth of root or shoot organ cultures was not attempted. Other work has shown the ability of sugar beet cells (callus and suspension) to habituate to hormone-free medium by successively lowering the auxin concentration, however the ability to grow without exogenous cytokinins appeared to be spontaneous in most of these cultures (Van Geyt and Jacobs, 1985). Doubling times of these cell cultures ranged from 4 to 8 days, similar to that of the rye root cultures reported here.…”
Section: Discussionsupporting
confidence: 59%
“…It has been shown that during long-term culture, plant cells may lose the need for auxin and/or cytokinin to maintain active growth. This process known as 'habituation', which is common in callus cultures in some plant species such as sugarbeet [ 50 ], was described as a shift from auxo- to autotrophic state for growth regulator requirements [ 51 ]. Coffee embryogenic cultures do not require auxin or cytokinin to proliferate, although it was possible to stimulate proliferation by optimum exogenous concentrations of both growth regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Habituation or autonomy for one or several exogenous growth regulators characterizes some callus types which is not without relation with their anatomical structure [9]. Callus anatomical and biochemical characteristics certainly can be affected by the culture media and the environmental conditions since they can be changed by chemical and physical manipulations [8,38]. There are, however, some indications that calli may continue to express biochemical traits of the mother plants [14,22,36,40].…”
Section: Introductionmentioning
confidence: 99%